2000
DOI: 10.1081/ddc-100102311
|View full text |Cite
|
Sign up to set email alerts
|

Study of Biodistribution of Methotrexate-Loaded Bovine Serum Albumin Nanospheres in Mice

Abstract: Nanospheres made from natural hydrophilic polymers have been proved efficient in terms of better drug-loading capacity, biocompatibility, and possibility less opsonization by reticuloendothelial system (RES) through an aqueous stearic barrier. Hence, nanospheres containing methotrexate were prepared from bovine serum albumin (BSA) by a novel pH coacervation method. A drug-to-polymer ratio study was carried out to determine the carrier capacity. The batch with the highest drug loading was subjected to in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The use of natural carriers can avoid reticuloendothelial system uptake. Previous studies on biodistribution of some nanoparticles revealed that the nanoparticles protected by serum albumin (human serum albumin or BSA) exhibited high retention in liver, lung, and spleen . In this study, the BSA‐protected AuNC also showed relatively high retention in these organs besides in the tumor region.…”
Section: Resultssupporting
confidence: 51%
“…The use of natural carriers can avoid reticuloendothelial system uptake. Previous studies on biodistribution of some nanoparticles revealed that the nanoparticles protected by serum albumin (human serum albumin or BSA) exhibited high retention in liver, lung, and spleen . In this study, the BSA‐protected AuNC also showed relatively high retention in these organs besides in the tumor region.…”
Section: Resultssupporting
confidence: 51%
“…Smaller particles, including nanoparticles, however, can be accumulated in the lung by agglomeration due to breakdown of repulsive forces between the particles. Several studies have demonstrated accumulation of nanoparticles in the lung [15][16][17][18].…”
Section: Passive Targetingmentioning
confidence: 99%
“…After standard solvents used for intravenous formulations failed to keep CCF642 in solution, we explored albumin, an abundant plasma protein with hydrophobic and hydrophilic surfaces. Albumin is FDAapproved as carrier for paclitaxel in Abraxane and bovine as well as human albumin has been used in mice effectively for drug delivery (34,35). Albumin-dissolved CCF642 could be given intravenously without injection reactions in mice, but for ease of administration, we chose the intraperitoneal route and saw promising efficacy without obvious toxicity.…”
Section: Discussionmentioning
confidence: 99%